Modern Concepts on Orientational Phenomena in Forming Products from Thermoplastic Materials: Konsep Modern tentang Fenomena Orientasi dalam Pembentukan Produk dari Bahan Termoplastik - Rosilov Mansur Sirgiyevich; Sultonov Oybek Komiljonovich (Academia Open, 2022)
This study investigates the biaxial orientation of films, with a focus on deformation within the plane. By employing microscopy and diffraction analysis, the average degree of orientation in each direction was determined, revealing a consistently biaxially oriented structure. The surface layers exhibited the highest degrees of orientation. These findings have implications for understanding film mechanics and performance, aiding in the development of improved manufacturing processes and materials for various industrial applications. Highlights: The study investigates biaxial orientation in films, focusing on deformation within the plane. Microscopy and diffraction analysis determine the average degree of orientation and reveal higher orientation in the surface layers. Implications include improved understanding of film mechanics, aiding in the development of materials for diverse industrial applications. Keywords: Biaxial orientation, Films, Deformation, Surface layers, Industrial applications.